(untitled) (Economic studies journal, 2020)
Commercial banks are considered one of the most important financial institutions providing funding, especially in developing countries .The study aimed to evaluate the banking performance using the liquidity, operating ratios and profitability ratios of both the United Bank and the Sahary Bank, following the descriptive compare analytical approach. The secondary data was relied on for the study period (2011-2014) through the financial statements of banks and used the ratios of liquidity, operating ratios and profit as a tool for data analysis, the study sample was the United Bank for Trade and Development and the Sahary Bank. Results were the liquidity ratios of the United Bank were high during the study years and a decrease in the investment rate in short-term securities, while the results indicated an increase in operating ratios in the Sahara Bank compared to the United Bank, but the profitability ratios of the United Bank were higher than the profit rates of Sahara Bank. The study recommends the necessity of diversification in the fields and methods of financing and investment for banks in order to reduce risks and increase their profitability